Upaya Pengendalian Wereng Batang Coklat Melalui Penataan Kelembagaan Kelompok Tani - Yati Astuti; Hijriah Mutmainah; Eka Yuli Susanti; Sri Kurniawati (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
The problem of loss of rice production due to brown planthopper (BP) attacks every year always appears and is felt to be completely unresolved. Many factors cause the lack of success of BP control, one of which is the understanding of farmers on the characteristics of BP, monitoring and control technology is still lacking and the existing farmer group institutions are not yet well established. The purpose of this study is to build a model/pilot of institutional arrangement for farmer groups in solving the problem of yield loss caused by brown planthoppers. The methodology used begins with extracting information on existing technology through focus group discussions, implementing a pilot BP control technology in the form of a 5 ha field laboratory, implementing a field school for 6 meetings, empowering farmer institutions through the formation of pest observer teams and advocacy for pesticide store. The study was conducted in Pamarayan Village, Suka Tani IV Farmer Group, Pamarayan Village, Pamarayan District, Serang Regency, Banten Province in January-December 2019. Data collection was carried out through field observations and filling out questionnaires in the form of pre/post test. The data obtained were analyzed descriptively. The results of the study showed that there was an increase in the knowledge and skills of cooperative farmers in rice cultivation and WBC control technology by 26.53-70.71% and an increase in knowledge and skills of the pest observer team by 79.49-96.77%. The technological and institutional performance of farmer groups succeeded in increasing rice production by 55.63% in MK I and 97.5% in MK II compared to before the program was implemented. It is hoped that this WBC control model can be replicated in other WBC endemic areas.